Permanent draft genome of Thermithiobacillus tepidarius DSM 3134T, a moderately thermophilic, obligately chemolithoautotrophic member of the Acidithiobacillia. Issue 1 (December 2016) - Boden, Rich; Hutt, Lee; Huntemann, Marcel; Clum, Alicia; Pillay, Manoj; Palaniappan, Krishnaveni; Varghese, Neha; Mikhailova, Natalia; Stamatis, Dimitrios; Reddy, Tatiparthi; Ngan, Chew; Daum, Chris; et al.
Abstract Thermithiobacillus tepidarius DSM 3134T was originally isolated (1983) from the waters of a sulfidic spring entering the Roman Baths (Temple of Sulis-Minerva) at Bath, United Kingdom and is an obligate chemolithoautotroph growing at the expense of reduced sulfur species. This strain has a genome size of 2, 958, 498 bp. Here we report the genome sequence, annotation and characteristics. The genome comprises 2, 902 protein coding and 66 RNA coding genes. Genes responsible for the transaldolase variant of the Calvin-Benson-Bassham cycle were identified along with a biosynthetic horseshoein lieu of Krebs' cyclesensu stricto . Terminal oxidases were identified, viz. cytochromec oxidase (cbb 3, EC 1.9.3.1) and ubiquinol oxidase (bd, EC 1.10.3.10). Metalloresistance genes involved in pathways of arsenic and cadmium resistance were found. Evidence of horizontal gene transfer accounting for 5.9 % of the protein-coding genes was found, including transfer fromThiobacillus spp. andMethylococcus capsulatus Bath, isolated from the same spring. Asox gene cluster was found, similar in structure to those from otherAcidithiobacillia – by comparison withThiobacillus thioparus andParacoccus denitrificans, an additional gene betweensoxA andsoxB was found, annotated as a DUF302-family protein of unknown function. As the Kelly-Friedrich pathway of thiosulfate oxidation (encoded bysox ) is not used inThermithiobacillus spp., the role of the operon (if any) in this species remains unknown. We speculate that DUF302 andsox genes may have a role in periplasmic trithionate oxidation.